11x-7y+3=4x-4y-3

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Move all terms containing y to the left side of the equation.

Add 4y to both sides of the equation.

11x-7y+3+4y=4x-3

Add -7y and 4y.

11x-3y+3=4x-3

11x-3y+3=4x-3

Move all terms not containing y to the right side of the equation.

Subtract 11x from both sides of the equation.

-3y+3=4x-3-11x

Subtract 3 from both sides of the equation.

-3y=4x-3-11x-3

Subtract 11x from 4x.

-3y=-7x-3-3

Subtract 3 from -3.

-3y=-7x-6

-3y=-7x-6

Divide each term by -3 and simplify.

Divide each term in -3y=-7x-6 by -3.

-3y-3=-7x-3+-6-3

Cancel the common factor of -3.

Cancel the common factor.

-3y-3=-7x-3+-6-3

Divide y by 1.

y=-7x-3+-6-3

y=-7x-3+-6-3

Simplify each term.

Dividing two negative values results in a positive value.

y=(7)x3+-6-3

Divide -6 by -3.

y=7×3+2

y=7×3+2

y=7×3+2

Rewrite in slope-intercept form.

y=73x+2

y=73x+2

Using the slope-intercept form, the slope is 73.

m=73

Find the Slope 11x-7y+3=4x-4y-3